Aggression by convict cichlid pairs as a means to deter brood mixing in a natural setting. (April 2020) - van Breukelen, Natalie A.; Santangelo, Nicholas
Abstract : Parental aggression can be a costly behaviour and flexible based upon context. While defence of offspring from potential predators has been well studied in the convict cichlid, it is unclear why parents are aggressive towards other parental pairs who are not likely to be offspring predators. In this experiment we explore the aggressive behaviour of pairs towards parental pairs and nonparental individuals using experimental presentations in the field. We found that parental pairs showed more aggressive displays towards other parental pairs than towards nonparental individuals. Bites did not differ between treatments, but there was a sex difference in bites, with males preferring to bite males and females showing no preference. As a higher level of display was observed both in the presence and absence of fry, we also examined the pair response to fry alone. Focal pairs were more aggressive to stimulus fry that were larger than their own fry, indicating that the larger stimulus fry represented a risk to the focal pair, as predicted by previous findings on brood mixing. We conclude that pair aggression towards parental pairs is a means to prevent brood mixing, and the greater aggression shown towards parental pairs suggests that the risk to parental pairs of brood mixing is greater than that of fry predation by nonparental fish. Highlights: We studied context-dependent decisions of biparental defence in convict cichlids. Parents were more aggressive to other parental pairs than to nonparental adults. Parents were also more aggressive to fry that were larger than their own. Pair aggression towards parental pairs appears to be a means to prevent brood mixing. Parents appear more threatened by brood mixing than by potential fry predation.